2023
DOI: 10.13048/jkm.23010
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Ultrasound-guided Bee Venom Pharmacopuncture on Plantar Fasciitis

Abstract: Objectives: This study is to report the usefulness of ultrasound in diagnosing plantar fasciitis and the effectiveness of ultrasound-guided bee venom pharmacopuncture as a treatment of it.Methods: A 61-year-old woman suffered from plantar fasciitis on her right foot for 1 month. The sonographic findings were fascial thickening, blurring of perifascial border and perifascial effusion. The ultrasound-guided bee venom pharmacopuncture for 6 times and conventional Korean medicine therapies like acupuncture and mox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…[8] In Korea, several retrospective studies reported positive effects of ultrasoundguided pharmacopuncture for the treatment of various musculoskeletal disorders, such as rib fracture and acute lower back pain. [9][10][11][12][13][14][15] Through these reports, it can be inferred that ultrasoundguidance is actively applied in the clinical practice of KM. Fueled by the rapid development of science and technology, new technologies have been and adopted in medicine through multidisciplinary collaboration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] In Korea, several retrospective studies reported positive effects of ultrasoundguided pharmacopuncture for the treatment of various musculoskeletal disorders, such as rib fracture and acute lower back pain. [9][10][11][12][13][14][15] Through these reports, it can be inferred that ultrasoundguidance is actively applied in the clinical practice of KM. Fueled by the rapid development of science and technology, new technologies have been and adopted in medicine through multidisciplinary collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In Korea, several retrospective studies reported positive effects of ultrasound-guided pharmacopuncture for the treatment of various musculoskeletal disorders, such as rib fracture and acute lower back pain. [9–15]…”
Section: Introductionmentioning
confidence: 99%
“…한의사는 초음파 영상진단을 통한 침술, 도침, 약침 등 중재를 시행하여, 이전보다 정밀한 시술을 통한 안전성과 효과성 증대를 기대할 수 있어 최근 임상에서 활용 범위가 확산되고 있다 5) . 현재까지 족저근막염 6) , 견관절 질환 7) , 늑골 골절 8) , 경추 9) , 요추 1). 1).…”
unclassified